Resolvendo os cubos prisioneiros - Borges, Robinson (2015)
This work shows how an educational toy (game) can stimulate the teaching of mathematics. This game becomes a starting point for several discussions, is a pedagogical tool that relates to concrete, direct and simple way, various parts of mathematics. This is a game easy to use, easy to manufacture and which favors the systematization of logical reasoning. By using this teaching tool the student is required to take decisions and also notes that every decision has implications in the upcoming decisions. The desired solution is obtained with the aid of a spreadsheet. We work with a general case and for that we used twenty-four variables. To reach the desired solutions toy was converted into codes, axes were used as directions and guidelines senses them, counting rule, application of the fundamental theorem of arithmetic and foundations of probability.